G375(P) Hypertension in the paediatric renal transplant population: An audit cycle. (7th April 2014) - Mallett, T; O'Hagan, E; Harvey, C; McCormick, C; McKeever, K
Abstract : Hypertension in the paediatric renal transplant paediatric population can have significant adverse effects on transplanted kidney function in addition to general and cardiovascular health. The British Association of Paediatric Nephrologists (BAPN) guidelines recommend maintaining blood pressure below the 90 th percentile in this population. An audit of all paediatric renal transplant recipients in the Royal Belfast Hospital for Sick Children assessed current practice of hypertension management against BAPN guidelines. Blood pressure recordings from the most recent clinic attendance were noted and the percentile calculated using the National Heart Lung and Blood Institute paediatric blood pressure charts. We assessed the blood pressure percentile in our transplant population against the audit standard, the BAPN guidelines. The audit identified 15% of the transplant recipients to have blood pressures above their target range. Other areas for improvement included availability of appropriate sized blood pressure cuffs at outpatient clinics, clinician ability to recognise hypertension and resources to confirm if isolated blood pressure measurements reflected true hypertension in individuals. The results of the audit were presented at a multidisciplinary meeting with all renal health professionals engaged in the implementation of changes. Recommendations included ensuring availability of all sizes of blood pressure cuffs, prominent placement of blood pressure percentile charts in all clinic rooms, the creation of a renal transplant clinic stamp to encourage target BP recording and recognition of hypertension and the development of a new ambulatory blood pressure monitoring service. All of the age-appropriate renal transplant patients were invited to have ambulatory blood pressure monitoring (ABPM) and hypertension information leaflets were developed with practical advice reiterated through the dietician and clinician at clinic. After one year the audit cycle was completed. All children identified as being hypertensive were now meeting their target blood pressure. In addition, all age-appropriate assenting patients had ABPM performed, which identified previously undiagnosed hypertensive patients ensuring appropriate treatment. A clinic has now been established for yearly ABPM of all post-transplant patients. By identifying simple measures to improve the measurement of blood pressure and aid the recognition of hypertension in children, we have reduced the degree of hypertension in this transplant population, thereby helping to optimise cardiovascular health and graft survival.